To trust, or not to trust? Individual differences in physiological reactivity predict trust under acute stress - Potts, Stephanie R.; McCuddy, William T.; Jayan, Devi; Porcelli, Anthony J. (Psychoneuroendocrinology, 2019)
•The Trust Game was performed after exposure to two acute stressors or a control.•Acute stressors were between-subjects with or without a social evaluative component.•This occurred at short or long latencies to dissociate stress response reactivity.•Acute stress was associated with reduced trust overall.•However, individual differences in reactivity predicted increased trust. The stress response represents an evolutionarily ancient array of biological responses to challenge or threat that facilitate survival by promoting adaptive behaviors. ‘Adaptive’ in the evolutionary sense, however, does not easily translate to explain stress’ effect on human decisions. Much research demonstrates that acute stress alters decision-making, but outcomes are obscured by a range of methodological factors. Further, less is known about how stress affects decision-making in social contexts in which people so often act. This is of great importance in today’s increasingly complex social environment, replete with potential stressors, where cooperation and trust are critical. Here the aim was to explore acute stress’ effect on prosocial decision-making, while also controlling for methodological factors that may contribute to varied research outcomes. Ninety-six participants were exposed between-subjects to acute stressors with or without a significant social evaluative component, or a control procedure, after which they performed a variant of the Trust Game (a social decision-making task requiring cooperation and trust with a ‘partner’). Task performance occurred at different times with respect to exposure to examine the roles of temporally distinct biological stress pathways. Overall acute stress was associated with reduced trust, but a more complex pattern emerged when accounting for individual differences in physiological stress responses via multivariate analysis. In keeping with the complexity of stress itself, acute stress may enhance or reduce propensity to trust based on an individual’s unique pattern of physiological reactivity.